Fusion, fission, and scrambling of the bilaterian genome in Bryozoa - Lewin, Thomas D.; Liao, Isabel Jiah-Yih; Chen, Mu-En; Bishop, John D.D.; Holland, Peter W.H.; Luo, Yi-Jyun (Genome Research, 2025)
Groups of orthologous genes are commonly found together on the same chromosome over vast evolutionary distances. This extensive physical gene linkage, known as macrosynteny, is seen between bilaterian phyla as divergent as Chordata, Echinodermata, Mollusca, and Nemertea. Here, we report a unique pattern of genome evolution in Bryozoa, an understudied phylum of colonial invertebrates. Using comparative genomics, we reconstruct the chromosomal evolutionary history of five bryozoans. Multiple ancient chromosome fusions followed by gene mixing led to the near-complete loss of bilaterian linkage groups in the ancestor of extant bryozoans. A second wave of rearrangements, including chromosome fission, then occurred independently in two bryozoan classes, further scrambling bryozoan genomes. We also discover at least five derived chromosomal fusion events shared between bryozoans and brachiopods, supporting the traditional but highly debated Lophophorata hypothesis and suggesting macrosynteny to be a potentially powerful source of phylogenetic information. Finally, we show that genome rearrangements led to the dispersion of genes from bryozoan Hox clusters onto multiple chromosomes. Our findings demonstrate that the canonical bilaterian genome structure has been lost across all studied representatives of an entire phylum, and reveal that linkage group fission can occur very frequently in specific lineages.